OxyR positively and directly regulates Vi polysaccharide capsular antigen in Salmonella enterica serovar Typhi. (November 2018) - Zhang, Ying; Chong, Xiaodan; Xia, Lin; Lu, Renfei; Osei-Adjei, George; Zhang, Yiquan; Huang, Xinxiang
Abstract: Salmonella enterica serovar Typhi ( S. Typhi) is a human enteropathogen that can overcome oxidative stress and survive in macrophages. OxyR is an important part of the antioxidant defense system. S. Typhi expresses a virulence (Vi) polysaccharide capsular antigen, which provides the bacterium with the ability to avoid host defenses and suppress detection by the innate immune system. This study investigated the effect of OxyR on Vi antigen in S . Typhi. In the oxyR mutant strain, microarray analysis, quantitative real time PCR and β-galactosidase assay confirmed that the viaB operon was positively regulated by OxyR. The Vi enzyme-linked immunosorbent assay and flow cytometry results showed that Vi capsule level was decreased in the oxyR mutant strain. Also, the EMSA revealed that OxyR directly binds to the promoter region of tviA . Thus, we propose that S. Typhi OxyR positively regulates expression of Vi capsule antigen in a direct manner. Highlights: In S. Typhi, the mRNA level of viaB operon was decreased in oxyR mutant strain. Vi capsule level was decreased in the oxyR mutant strain. OxyR directly binds to the promoter regions of tviA. OxyR positively regulates expression of Vi capsule antigen in a direct manner.